MIDWIFERY STUDENTS’S INTEREST ON MIDWIFERY PROFESSIONAL EDUCATION - Aninda Regita Putri Darna; Budi Utomo; Endyka Erye Frety (Indonesian Midwifery and Health Sciences Journal, 2021)
AbstractBackground: Midwifery education in Indonesia consists of D3, D4, S1 and professional education levels. Midwifery professional education is a midwifery education that was only established in 2008. The low interest in midwifery professional education makes it difficult for midwifery education in Indonesia to develop. This study aims to identify interest from another point of view as an effort to increase interest in midwife professional education. Methods: This study is a qualitative study with a phenomenological design. Determination of research subjects was done by purposive sampling technique and obtained 10 midwifery students from transfer class year 2019 Universitas Airlangga. The data was collected by online in-depth interviews with research instruments were voice recorder, notebooks, and interview guides. Data analysis was performed by using data reduction techniques, determining themes, presenting data descriptively, and drawing conclusions. Results: Midwifery students' interest in midwifery professional education was different, namely very interested, interested and in the between of interested not interested. This interest arises based on the factors of inner urge, the factors of social motive, emotional factors and awareness of the importance of midwife professional education. Conclusion: Based on the perceptions of midwifery students from transfer class about the picture of midwifery professional education, midwifery students think that it is necessary to increase graduates of midwifery professional education in Indonesia which shape the interest of midwifery students to take part in midwifery professional education.